Size Distribution and Length-Weight Relationship of Red Snapper (Lutjanus malabaricus) in Pinrang Waters Regency of Pinrang - Nuraeni L Rapi; Mesalina Tri Hidayani; Djumanto Djumanto; Murwantoko Murwantoko (Agrikan: Jurnal Agribisnis Perikanan, 2019)
Fisheries activities red snapper in Pinrang waters is considered to be a small scale and caught with that variety of types instrument catch fish (multi gears) one of them is bubu fishing gear. Now, the level of the utilization of red snapper is believed to have been experience symptoms of over fishing due to the high pressure in the area. The study aims to analyze the size structure and length-weight correlation of red snapper (Lutjanus sp). The study was conducted during 5 months of period, starting from March to July 2019 in Pinrang waters, Pinrang District. The sample of the fish obtained by fishermen using ‘Bubu’ fishing gear. The results showed that the total length structure of males and females of the red snapper was ranging from 32 - 57 cm, while the weight structure of males and females of the red snapper had a wide range from 500 to 2500 grams. The total sample of the red snapper is 163 divided into 68 males and 95 females. The growth pattern of red snapper can be categorized in a negative allometric type with a value of b = 2.3328 which means that the length increased faster than the weight gain.